Mechanically stable ultrafiltration membrane and method for preparing the same

By forming a multi-layer coating structure on the support layer of the ultrafiltration membrane and using non-solvent gas to generate damping areas, the problem of insufficient impact resistance of the ultrafiltration membrane is solved, and higher impact resistance and longer use are achieved. life.

CN114173911BActive Publication Date: 2025-02-21SARTORIUS STEDIM BIOTECH GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080055414.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-30
Filing Date
2020-07-29
Publication Date
2025-02-21
Estimated Expiration
2040-07-29

AI Technical Summary

Technical Problem

Ultrafiltration membranes exhibit low impact resistance during impact, resulting in short life and lack of stability in some demanding applications.

Method used

By forming a multi-layer coating structure on the support layer, the non-solvent gas acts on the first polymer layer to create a damping region, and applying the second polymer layer after a time delay, the impact resistance of the film is enhanced.

Benefits of technology

The high impact resistance of the ultrafiltration membrane perpendicular to the filter surface is achieved, extending the membrane's service life and improving stability in demanding applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114173911B_ABST
    Figure CN114173911B_ABST
Patent Text Reader

Abstract

The present invention relates to a mechanically stable ultrafiltration membrane and a method for producing such an ultrafiltration membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a mechanically stable ultrafiltration membrane and a method for preparing the same.

[0002] Filtration membranes are classified according to their retention properties and pore size. Thus, based on pore size, a distinction is usually made between microfiltration membranes (average pore size: 0.1 to 10 μm), ultrafiltration membranes (average pore size: 0.01 to less than 0.1 μm), nanofiltration membranes (average pore size: 0.001 to less than 0.01 μm) and reverse osmosis membranes (average pore size: 0.0001 to less than 0.001 μm) (see Shang-Tian Yang, Bioprocessing for Value-Added Products from Renewable Resources, 2007).

[0003] In terms of the retention properties of the membrane, a similar definition can be made based on the molecular weight cut-off (MWCO). The MWCO relates to the dissolved substance (usually dextran) with the lowest molecular weight in Daltons, where 90% of the dissolved substance is retained by the membrane, or to the molecular weight of the molecule in Daltons, where 90% of the molecules with this molecular weight are retained by the membrane. For example, a membrane with a MWCO of 10 kDa retains at least 90% of dextran of 10 kDa and larger.

[0004] During their regular use, ultrafiltration membranes may often be subjected to shocks, which are caused by vibrations of pumps or other equipment components during, for example, cross-flow processes. However, many ultrafiltration membranes exhibit low shock resistance perpendicular to the filter surface and therefore have a short lifespan and lack sufficient stability for certain demanding applications.

[0005] Therefore, an object of the present invention is to provide an ultrafiltration membrane having high impact resistance perpendicular to the filter surface, and also to provide a method for preparing such an ultrafiltration membrane.

[0006] This object is achieved by the embodiments described in the claims.

[0007] The present invention more particularly relates to a method for preparing an ultrafiltration membrane, said method comprising the following steps:

[0008] (a) applying a first polymer solution to a support layer to form a first polymer layer on the support layer and / or partially or completely in the support layer,

[0009] (b) contacting the coated support layer from step (a) with a gas comprising a non-solvent for the polymer in the first polymer solution,

[0010] (c) applying a second polymer solution to the first polymer layer to form a second polymer layer on the first polymer layer, and

[0011] (d) introducing the multi-layer coated support layer into a precipitation bath comprising a precipitation agent relative to the polymer in the first polymer solution and / or the second polymer solution (4).

[0012] According to the method of the present invention, an ultrafiltration membrane with high impact resistance perpendicular to the filter surface can be obtained. This distinguishes it from known ultrafiltration membranes (e.g., ultrafiltration membranes prepared by conventional double coatings). In the method of the present invention, a gas containing a non-solvent acts on the first polymer layer (initial coating), thereby producing a damping region in the first polymer layer. Only in the case of a time delay is the second polymer layer (main coating) applied. The brief contact with the gas containing a non-solvent in step (b) provides the ultrafiltration membrane with a damping region and produces a membrane with enhanced impact resistance.

[0013] In the present invention, the term "ultrafiltration membrane" refers to a membrane having a MWCO of 1 kDa to 1000 kDa.

[0014] According to the present invention, in step (a) and step (c), a first polymer solution and a second polymer solution are applied to a support layer and a coated support layer, respectively, to form a first polymer layer on the support layer and / or partially or completely in the support layer, and to form a second polymer layer on the first polymer layer, respectively.

[0015] The polymer solution used to prepare the ultrafiltration membrane is not subject to any particular restrictions. Thus, any solution of one or more polymers suitable for membrane formation can be used.

[0016] The polymer (film-forming polymer) in the dissolved polymer solution is preferably a cellulose derivative selected from cellulose esters, cellulose nitrate and regenerated cellulose. The polymer solution may contain one or more, preferably one, of these film-forming polymers independently of one another. Examples of cellulose esters are cellulose acetates, such as cellulose monoacetate, cellulose diacetate and cellulose triacetate, cellulose propionate, cellulose butyrate and cellulose acetobutyrate.

[0017] The solvents for the polymer solution are not subject to any particular restrictions, provided that they are able to dissolve the corresponding polymer or polymers. The solvent for the corresponding film-forming polymer (or for each film-forming polymer) preferably has a solubility of at least 2 wt %, more particularly at least 5 wt %, more preferably at least 10 wt %, more preferably at least 20 wt %, very preferably at least 30 wt % under standard conditions (25° C., 1013 hPa). Suitable solvents are known to those skilled in the art. Suitable solvents for cellulose acetate are, for example, ketones (e.g. acetone), dioxanes, amides (e.g. dimethylacetamide (DMAc), N,N-dimethylpropionamide, 2-hydroxy-N,N-dimethylpropionamide) and N-butylpyrrolidone and mixtures thereof. Suitable solvents for cellulose nitrate are, for example, acetone and ethyl acetate.

[0018] The polymer solution can also include one or more auxiliary agents independently of each other. Suitable auxiliary agents are, for example, swelling agents, solubilizing agents, hydrophilic agents, pore formers (porogens) and / or non-solvents for corresponding polymers. These types of auxiliary agents are well known to those skilled in the art and are suitable for film-forming polymers. For example, polyethylene glycol (PEG), particularly PEG1000 or PEG2000, glycerol or polyvinylpyrrolidone (PVP) can be used as swelling agents or pore formers. The polymer solution is preferably composed of corresponding film-forming polymers, solvents and optional one or more auxiliary agents (preferably pore formers, swelling agents and / or non-solvents) independently of each other.

[0019] The term "non-solvent" herein refers to a liquid which is incapable of dissolving the film-forming polymer. The non-solvent for the (or each) film-forming polymer preferably has a solubility (respectively) of at most 1 wt%, very preferably at most 0.1 wt% under standard conditions.

[0020] If the polymer solution comprises a non-solvent for the corresponding film-forming polymer (or another precipitant), the maximum concentration of the non-solvent (or precipitant) is a concentration which is insufficient to cause precipitation of the film-forming polymer. The polymer solution preferably consists independently of one another of a solvent for the corresponding film-forming polymer, the corresponding film-forming polymer and a non-solvent (mixture).

[0021] Suitable non-solvents are, for example, water, glycerol, isopropanol, ethanol and mixtures thereof. Suitable non-solvents for cellulose acetate are, for example, water, glycerol, isopropanol, ethanol (with reduced non-solvent properties) and mixtures thereof. Suitable non-solvents for cellulose nitrate are, for example, water and alcohols. Unless otherwise indicated, the above definitions and embodiments relating to non-solvents apply equally to all aspects of the invention.

[0022] The solid content in the polymer solution is not subject to any particular restrictions and can be selected based on, for example, the desired type of filter. The term "solid content" herein refers to the amount of pure film-forming polymer present. In a preferred embodiment, the polymer solutions independently of one another have the same or different solid contents of 2 wt % to 40 wt %, more particularly 5 wt % to 30 wt %, still more preferably 7 wt % to 20 wt %, very preferably 10 wt % to 16 wt %.

[0023] The polymer solutions can have different solid contents, which can be selected based on, for example, desired film properties. In a preferred embodiment, the first polymer solution has a higher solid content than the second polymer solution. For example, the first polymer solution can have a solid content of 10 wt % to 30 wt %, and the second polymer solution has a solid content of 5 wt % to 20 wt %, wherein the first polymer solution has a higher solid content than the second polymer solution.

[0024] The viscosity of the polymer solution is not subject to any particular restrictions. For example, the polymer solutions independently of one another may have a viscosity of 800 to 40000 mPa*s, more particularly 1000 to 25000 mPa*s, very preferably 3000 to 15000 mPa*s.

[0025] The polymer solution does not have to be subjected to any defined thermal pretreatment, ie, it does not have to be formed into a film / structure using thermal pretreatment. More particularly, the polymer solution preferably does not have any lower or upper critical solution temperature.

[0026] Methods for applying polymer solutions are known to the person skilled in the art from the prior art and can be used without particular restrictions in the method of the invention (e.g. in step (a) and step (c)). Such methods are, for example, methods in which the (coated) support layer is conveyed through, for example, a doctor blade system or a slot die, from which the corresponding polymer solution emerges. Step (a) is preferably carried out using a slot die. Step (c) is preferably carried out using a slot die.

[0027] According to the invention, in step (a), a first polymer solution (2) is applied to a support layer (1) to form a first polymer layer on the support layer (1) and / or partially or completely in the support layer (1). This produces a (single) coated support layer (e.g. Figure 1 In step (c) according to the present invention, the second polymer solution (4) is applied to the first polymer layer to form a second polymer layer (as shown) on the first polymer layer. Figure 1 This results in a multi-layer coated support layer.

[0028] In step (a), the first polymer solution may partially or completely penetrate into the support layer. For example, the first polymer layer may penetrate into the support layer to an extent of at least 25%, more particularly at least 50%, very preferably at least 75%.

[0029] The support layer may be conveyed by a carrier which is not subject to any particular restrictions. Any carrier suitable for the membrane preparation process of the prior art may be used. The carrier preferably has a flat surface and is inert with respect to the substances used (e.g., polymer solution and its components). Preferably used as a carrier are moving belts (conveyor belts) or drums (e.g., Figure 1 ), thereby enabling continuous method implementation.

[0030] In a preferred embodiment, the support layer in step (a) and the coated support layer in step (c) are moved relative to the respective polymer solution at a speed of 30 to 500 m / h, more particularly 60 to 400 m / h, very preferably 100 to 300 m / h during their application. In other words, the (coated) support layer is conveyed at the above-mentioned speeds on, for example, a doctor blade system or a slot die for applying the respective polymer solution.

[0031] The application temperatures in step (a) and step (c) are not subject to any particular limitation. For example, the application temperatures may be independently 4°C to 40°C.

[0032] According to the invention, in step (b), the coated support layer from step (a) is contacted with a gas (3) comprising a non-solvent (e.g. Figure 1 Unless otherwise indicated, the above definitions and embodiments of the non-solvent also apply to the non-solvent contained in the gas. Step (b) is preferably carried out under defined conditions.

[0033] Preferably, phase separation in the first polymer solution (2) occurs due to contact with the gas containing the non-solvent. The term "phase separation" herein refers to a phase separation that produces an initial structure in the cast film (applied polymer solution), which means that it restricts the movement of polymer chains.

[0034] Due to any phase separation in the first polymer layer, the adhesion of the second polymer layer to the first polymer layer may be reduced. However, adhesion may be promoted by the interaction of the solvent of the second polymer layer with the phase-separated layer; that is, by appropriate choice of solvent when applying the second polymer solution, the thin phase-separated layer (of the first polymer layer) may be partially redissolved when the second polymer solution is applied, ensuring effective adhesion.

[0035] Herein, the content of the non-solvent gas is not subject to any particular limitation. For example, preferably at a temperature of 20° C., the gas may contain 1.0 to 20 g / m 3 , more particularly 1.7 to 18 g / m 3 , still more preferably 3.0 to 16 g / m 3 , very preferably 5.0 to 15 g / m 3 Preferably, at a temperature of 20°C, the gas may further contain 1.0 to 20 g / m 3 , more particularly 1.7 to 19 g / m 3 , still more preferably 5.0 to 18 g / m 3 , still more preferably 12 to 17 g / m 3 , very preferably 15 to 17 g / m 3 The non-solvent (absolute content of non-solvent) of the first polymer solution. When present, the remaining components of the gas (or gas mixture) are preferably inert relative to the material or equipment used. The remaining components of the gas (or gas mixture) can be, for example, nitrogen, air or other gases, preferably nitrogen. Preferably, not only (ambient) air is used as the gas containing the non-solvent relative to the polymer in the first polymer solution. The gas (or gas mixture) preferably does not contain oxygen. For example, based on the total amount of non-solvent, the gas containing the non-solvent relative to the polymer in the first polymer solution can contain or be composed of: nitrogen as a carrier gas and a non-solvent (mixture) composed of 50vol% to 100vol% of water and 0vol% to 50vol% of ethanol, preferably 80vol% to 100vol% of water and 0vol% to 20vol% of ethanol, very preferably 90vol% to 100vol% of water and 0vol% to 10vol% of ethanol.

[0036] The means that can be used to contact the coated support layer with the gas containing non-solvent are not subject to any particular restrictions. For example, the coated support layer can be guided through a chamber (for example, by means of a carrier), wherein the chamber has a suitable gas atmosphere and produces preferred limiting conditions in the chamber. The chamber contains the atmosphere of the load non-solvent, which is replaced to maintain the composition, but preferably no clear flow occurs. This can be achieved, for example, by a slight overpressure, which can be dissipated into the surrounding environment by a small gap. In the case of using a closed chamber, control in such a way that the replacement of the medium is carried out with gas moving through the chamber at a speed less than 0.2m / s and without generating eddy currents on the surface of the polymer layer.

[0037] The contacting can also be accomplished by supplying a suitable gas flow in the channel, for example, to produce the preferred defined conditions in the channel. Common gas supply techniques can be used here. The volume flow rate of the gas can be, for example, 10 to 600 m / s at a velocity of 0.3 to 8 m / s (v(gas)). 3 / h, preferably 150 to 300 m / s at a speed of 2.5 to 5 m / s 3 / h.

[0038] Preferably, step (b) is carried out by means of a channel. By means of the channel, an intentional overflow of the polymer layer can be introduced, wherein the gas is discharged from the chamber again after the overflow. The channel is preferably selected so that a defined flow (preferably laminar flow) of the gas containing the non-solvent impinges on the coated support layer at an angle of 0° to 45°, preferably 0° to 35°, very preferably 0° to 15°. The overflow can occur in the process direction or opposite to the process direction. The velocity of the gas in the channel is selected so that the effective overflow velocity is 0.3 to 8 m / s, preferably 2.5 to 5 m / s.

[0039] The action time in step (b) is not subject to any particular restrictions. The action time can be, for example, 500ms to 20s, more particularly 1.0s to 10s, very preferably 2.0s to 5.0s. When adopting the above-mentioned contact time, the desired properties of the ultrafiltration membrane can be developed in a particularly advantageous manner. In the case where the contact time is too long, a solid layer may have been formed, and therefore the precipitation properties may be changed or a (permeable) film may not be formed.

[0040] In a preferred embodiment, the action temperature in step (b) is at least 10° C. below the boiling point of the lowest boiling component of the first polymer solution (generally the solvent). According to the invention, the boiling point of the lowest boiling polymer solution component is above 50° C.; in other words, this polymer solution component is present in liquid form at 50° C. The corresponding action temperature is, for example, 10° C. to 40° C.

[0041] Preferably, the (diffusion) penetration depth of the non-solvent from the atmosphere formed by the gas containing the non-solvent in step (b) into the applied first polymer solution is less than 80% based on the total depth of the applied first polymer solution. The penetration depth is preferably at most 50%, more preferably at most 33%, most preferably at most 25%. The penetration depth is preferably at least 5.0%, more preferably at least 10%, most preferably at least 15%.

[0042] According to the invention, in step (d), the multi-layer coated support layer is introduced into a precipitation bath (5) (e.g. Figure 1), wherein the precipitation bath (5) contains a precipitant relative to the polymer in the first polymer solution (2) and / or the second polymer solution (4), preferably the second polymer solution (4). The precipitant used in step (d) is not subject to any particular restrictions. According to the present invention, the same precipitant as used in the conventional preparation method for the polymer film can be used. The precipitant causes the film-forming polymer to precipitate (phase inversion) in the first polymer layer and / or the second polymer layer. The precipitant can be a single compound or a mixture of two or more compounds. In the precipitation bath, the precipitant is preferably present in a liquid; particularly preferably, in the precipitation bath, the precipitant itself is a liquid, or the precipitation bath consists of the precipitant. The precipitant is preferably a non-solvent for the film-forming polymer or for each film-forming polymer of the two polymer solutions, wherein the precipitation bath is preferably composed of a precipitant selected from water, alcohol and water provided with additives; particularly preferably, the precipitation bath consists of water as a precipitant.

[0043] The temperature of the precipitation bath is not subject to any particular restrictions. For example, the temperature of the precipitation bath may be from 1°C to 60°C, more preferably from 3°C to 30°C, very preferably from 4°C to 20°C.

[0044] The method of the present invention may further comprise the following steps:

[0045] (c1) between step (c) and step (d), contacting the multilayer coated support layer from step (c) with a gas comprising a non-solvent for the polymer in the second polymer solution.

[0046] The above definitions and embodiments related to the non-solvent with respect to the polymer in the first polymer solution apply equally to the non-solvent with respect to the polymer in the second polymer solution.

[0047] In addition, the method of the present invention may include the following steps:

[0048] (e) After step (d), the multi-layer coated support layer is introduced into one or more rinse tanks (6).

[0049] (like Figure 1 exemplarily shown in ). The rinsing tank used in step (e) is not subject to any particular restrictions. According to the present invention, the same rinsing tank as used in the conventional preparation method of the polymer membrane can be used. The rinsing process is known to those skilled in the art and can be selected according to the requirements of the membrane (e.g., with respect to residual contaminants, extractables and leachables (extractable substances and leachable substances, respectively)). Suitable rinsing tanks can contain, for example, water, monohydric alcohols or polyhydric alcohols, or other hydrophilic liquids.

[0050] As mentioned above, one or more polymer solutions may contain cellulose esters. In order to obtain the corresponding hydrolyzate, the method of the present invention may further comprise the following steps:

[0051] (f) Hydrolyzing cellulose esters.

[0052] The hydrolysis method used in step (f) is not subject to any particular restrictions. According to the present invention, the same hydrolysis method as used in the conventional preparation method for polymer membranes can be used, for example, by introducing the support layer coated with multiple layers into an alkaline tank. Examples of common methods for hydrolysis are described in, for example, US-7422686-B2. Suitable alkaline tanks can include, for example, an aqueous solution or an alcohol solution of 50% KOH or a mixture thereof. The action time can be, for example, 1.0 to 30 minutes.

[0053] The method of the present invention may further comprise the following steps:

[0054] (g) Crosslinking the polymer chains in the polymer layer.

[0055] The cross-linking method used in step (g) is not subject to any particular restrictions. According to the present invention, the same cross-linking method as used in the conventional preparation method of the polymer film can be used. A suitable cross-linking method is, for example, cross-linking regenerated cellulose by the method described in US-7422686-B2.

[0056] The method of the present invention can be used to prepare an ultrafiltration membrane with more than two polymer layers. For this purpose, step (c) can be performed multiple times before step (d), in which case different or identical polymer solutions can be used. Therefore, the precipitation bath in step (d) can also include a precipitant relative to the polymer in other polymer solutions. Optionally, between multiple steps (c) independent of each other, there can be another step (b) in each case, wherein the corresponding gas includes a non-solvent relative to the polymer in the polymer solution applied immediately before. The number of steps (c) is correspondingly equal to or greater than the number of steps (b).

[0057] Another aspect of the present invention relates to an ultrafiltration membrane obtained by the method of the present invention for preparing an ultrafiltration membrane. The above definitions and embodiments also apply to this aspect of the present invention. The following definitions and embodiments also apply to the method of the present invention for preparing an ultrafiltration membrane. The ultrafiltration membrane of the present invention is preferably a flat membrane.

[0058] As mentioned above, the brief contact with the gas containing the non-solvent in step (b) of the method of the present invention provides the ultrafiltration membrane with a damping region and leads to its enhanced shock resistance. The shock resistance of the ultrafiltration membrane can be checked with reference to the occurrence of a convective pressure increase. The higher the proportion of the number of impacts of the test element that is tolerated by this ultrafiltration membrane without a convective pressure increase, the higher the shock resistance of the membrane. Therefore, the occurrence of a convective pressure increase is an indication of the instability of the ultrafiltration membrane in question.

[0059] This convective pressure rise can be determined by the following test methods (such as Figure 2 ). In this test, it is observed that the water-wetted ultrafiltration membrane (11) to be tested is introduced into the housing and sealed at the top and bottom. A cylindrical test element (K) with a diameter of 20 mm is repeatedly dropped onto the membrane (11) with a force of at least 1 N but not more than 250 N, preferably a force of 80 to 120 N, very preferably a force of 85 N, and thus produces an impact on the membrane (11). Above the membrane (11) (on the epidermis side or on the surface side), the pressure is P1, and below the membrane (11), the pressure is P2, where P1>P2 (for example, P1=3 bar, P2=1 bar). The sensor (S) detects the pressure increase (ΔP2) below the membrane (11). If the membrane (11) is intact, this pressure increase occurs as a result of diffusion. If the membrane (11) is broken due to the action of the test element (K), in addition to the diffusion component, there is also a convective component detected by the sensor (S). Thus, as soon as the membrane (11) is damaged by the impact of the test element (K), the convective component in addition to the diffuse component is detected by the sensor (S) for the pressure rise. The number of impacts at which the sensor (S) has detected this convective component is used as a measure of the impact resistance of the membrane (11) under investigation.

[0060] In a preferred embodiment of the ultrafiltration membrane of the present invention, the convective pressure rise determined by the above test method occurs at an impact number above 600, more preferably above 700, still more preferably above 800, most preferably above 900.

[0061] The ultrafiltration membrane of the present invention preferably has two or more, more preferably two polymer layers stacked on each other on a support layer, wherein the first polymer layer is directly arranged on the support layer and / or partially or completely arranged in the support layer, and the support layer has a damping region on one side adjacent to the second polymer layer arranged on the first polymer layer. The damping region is a part of the first polymer layer and is obtained by short contact with a gas containing a non-solvent in step (b) of the method of the present invention. Compared with the remaining regions of the first polymer layer, the damping region has a changed, preferably more ductile pore structure.

[0062] The supporting layer of ultrafiltration membrane is not subject to any particular restrictions. Therefore, all supporting layers known to those skilled in the art can be used. For example, the supporting layer can be a nonwoven web, a woven fabric or an open microfiltration membrane. The example of a nonwoven web is a polyolefin nonwoven, such as a PP / PE core-shell nonwoven and a polyester nonwoven. The microfiltration membrane can be made of, for example, polypropylene, polyethylene, polyamide, polyether sulfone or regenerated cellulose. The supporting layer is preferably a polyolefin nonwoven or a polyolefin membrane.

[0063] The thickness of the support layer may be, for example, 30 μm to 300 μm, more particularly 50 μm to 250 μm, very preferably 80 μm to 200 μm.

[0064] In a preferred embodiment of the ultrafiltration membrane of the present invention, the polymer layer has a sponge structure and the outermost polymer layer (i.e., the second polymer layer in the case of a double-layer membrane) has an outer retention surface layer (or skin) (on the sponge structure arranged below it). This sponge structure can be continuous or can be interrupted by a visible boundary layer. The term "sponge structure" herein means a structure in which the membrane matrix consists of an open fine network of polymer materials, with pores of similar size present in each layer, i.e., for example, not a finger or large void (macroporous) structure. The thickness of the outer retention surface layer is preferably 0.01 to 2.0 μm, more preferably 0.05 to 1.0 μm, and very preferably 0.1 to 0.50 μm. The average pore size of the outer retention surface layer is preferably 0.5 to 200 nm, more preferably 1.0 to 150 nm, and very preferably 2.0 to 100 nm.

[0065] The first polymer layer preferably has a microporous sponge structure with an average pore size of 0.05 to 30 μm, more preferably 0.1 to 10 μm, very preferably 1.0 to 5.0 μm. In addition, the sponge structure of the first polymer layer preferably penetrates the support layer by at least 25%, more preferably at least 50%, very preferably at least 75%.

[0066] The thickness of the first polymer layer is preferably 10 to 100 μm, more preferably 20 to 80 μm, very preferably 30 to 60 μm. The first polymer layer preferably penetrates into the support layer from 5 μm (given a minimum penetration of 25% and a minimum first polymer layer thickness of 20 μm) to 100 μm. The thickness of the combination of the first polymer layer and the support layer is preferably 50 to 350 μm, more preferably 80 to 250 μm, very preferably 100 to 200 μm.

[0067] The thickness of the damping region of the first polymer layer is not subject to any particular restrictions. For example, the damping region of the first polymer layer may account for up to 20% of the thickness of the first polymer layer. More particularly, the damping region of the first polymer layer may have a thickness of 0.1 to 20 μm, more preferably 0.5 to 10 μm, very preferably 1.0 to 5.0 μm. The thickness of the damping region of the first polymer layer can be varied, for example, by changing the non-solvent content in the gas or the action time in step (b) of the method of the present invention.

[0068] The thickness of the second polymer layer is preferably 20 to 100 μm, more preferably 30 to 80 μm, very preferably 35 to 70 μm. The thickness of the second polymer layer herein is preferably less than or equal to the combined thickness of the first polymer layer and the support layer. The average pore size of the second polymer layer (below the outer retaining surface layer) is preferably 0.1 to 20 μm, more preferably 0.2 to 10 μm, very preferably 0.5 to 5.0 μm.

[0069] The total thickness of the ultrafiltration membrane is not subject to any particular restrictions. For example, the total thickness of the ultrafiltration membrane is 50 to 400 μm, more particularly 80 to 350 μm, very preferably 120 to 300 μm.

[0070] The polymer layers can independently of one another have an asymmetric (pores widen in the course of the layer) or symmetrical sponge structure. In a preferred embodiment, the first polymer layer has an asymmetric sponge structure, which more preferably still resembles an hourglass (sand timer) (see Figure 6 ). The second polymer layer preferably has an asymmetric sponge structure. Most preferably, the polymer layers, preferably the first polymer layer and the second polymer layer, are combined together to have a composite structure (see Figure 6 ), wherein, starting from the first major surface, the pores first widen from passing through the membrane toward the nonwoven side, i.e., in the second polymer layer (asymmetric sponge structure), then the pores gradually taper inside the membrane, preferably above the nonwoven layer (into the first polymer layer), and the pores widen again during the structural change toward the second major surface, preferably in the nonwoven material.

[0071] As mentioned above, the film-forming polymer is preferably a cellulose derivative selected from cellulose esters, nitrocellulose and regenerated cellulose, which may be subjected to an optional hydrolysis and / or crosslinking process (optional steps (f) and (g) of the process of the invention). Accordingly, in a preferred embodiment of the ultrafiltration membrane of the invention, the polymer layer comprises a cellulose derivative selected from cellulose esters, nitrocellulose, regenerated cellulose and crosslinked regenerated cellulose. The polymer layer may comprise one or more, preferably one, of these polymers independently of one another. Very preferably, the polymer layer comprises cellulose esters, more particularly cellulose acetate, or crosslinked regenerated cellulose, and most preferably, they consist of them.

[0072] As mentioned above, the ultrafiltration membrane of the present invention can have more than two polymer layers. In this case, the outermost polymer layer has an outer retention surface layer. The embodiments and definitions of the second polymer layer can be similarly applied to other polymer layers. The lower (non-external) polymer layers can each have a damping region independently of each other.

[0073] The filtration capacity of the ultrafiltration membrane is not subject to any particular restrictions. For example, the filtration capacity can be adjusted by the pore size of the outer retention surface layer when necessary. The filtration capacity of the outer filter membrane can be designed, for example, so that the ultrafiltration membrane retains bovine serum albumin to a degree of no more than 50%.

[0074] There is no particular restriction on the possible uses of the membrane of the invention. It can be used for filtration, more particularly for filtering viruses, proteins or macromolecules.

[0075] The attached picture is as follows:

[0076] Figure 1 : Exemplary apparatus for carrying out the methods of the present invention

[0077] Figure 2 : Exemplary apparatus for carrying out the method for studying the impact resistance of a film (11)

[0078] Figure 3 : SEM image of the film of Example 1

[0079] Figure 4 : Zoom in from Figure 3 SEM images of the damping region (23, 33) and the sponge structure (22, 24) of the second polymer layer and the first polymer layer above / below the region

[0080] Figure 5 : Results of the method used to study the impact resistance of different ultrafiltration membranes (M-1 to M-3)

[0081] Figure 6 : Exemplary structures of the membranes of the present invention for different diffusion penetration depths (50%, 33%, 25%) of the gas containing the non-solvent in step (b)

[0082] The present invention is illustrated in more detail by the following non-limiting examples.

[0083] Determination of (average) pore size

[0084] To determine the (average) pore size of the membranes, a method based on analysis of membrane cross sections by scanning electron microscopy (SEM) was employed (described in P. Poelt et al., Journal of Membrane Science 2012, Vol. 399-400, pp. 86-94).

[0085] Example 1: Preparation of an ultrafiltration membrane with damping regions and enhanced impact resistance

[0086] A first polymer solution consisting of 75 wt% dimethylacetamide (DMAc), 15 wt% cellulose acetate (Acetati, Aceplast PC / FG type) and 5 wt% PEG1000, 5 wt% water was applied through a slot die to a PP / PE core-shell nonwoven (OMB-60; Mitsubishi) moving perpendicularly to the outlet opening at 100 m / h. The polymer film then passed through a chamber with a length of 10 cm, which contained an atmosphere with a relative humidity (rh) of 35% at a temperature of 20° C. After leaving the chamber, the polymer film was moved perpendicularly to the outlet opening of the second application medium (slide with a doctor blade) and a second polymer solution consisting of 78 wt% DMAc, 11 wt% cellulose diacetate (Acetati, Aceplast PC / FG type), 4 wt% PEG2000, 4 wt% glycerol and 3 wt% water was applied, which was then transferred to a precipitation bath consisting of water at a temperature of 6° C. for phase separation. The remainder of the above method was performed at room temperature.

[0087] The obtained membrane is then passed through multiple rinse tanks into a tank containing 50% KOH, in which the acetyl groups are hydrolyzed. Relative to comparable single-layer or multilayer membranes, the regenerated cellulose membrane has a specific stability in the z direction. By crosslinking, according to the method described, for example, in DE 102004053787A1, the membrane can be converted into a crosslinked regenerated cellulose membrane (cellulose hydrate membrane), which likewise has a specific mechanical stability. The SEM image of the obtained membrane is shown in Figure 3 and Figure 4 middle.

[0088] Embodiment 2: Study on the impact resistance of different ultrafiltration membranes

[0089] Two conventional ultrafiltration membranes (M-1 and M-2) of regenerated cellulose (RC) (a monolayer membrane (M-1) with a cut-off of 100 kDa, and a multilayer membrane (M-2) with a cut-off of 300 kDa, which were produced by a conventional co-casting process (double coating process) (without step (b)) and an ultrafiltration membrane (M-3) of regenerated cellulose according to the invention with a damping region and a cut-off of 300 kDa produced by the process according to the invention were subjected to the above-described test method for determining the resistance to shock or convective pressure rise. In this case, a pressure P1=3 bar and a pressure P2=1 bar were applied, and a cylindrical test element with a diameter of 20 mm was repeatedly dropped onto the membrane with a force of 85 N. The results obtained are plotted in Figure 5 It is shown that the ultrafiltration membrane (M-3) with a damping region according to the present invention can achieve much higher impact resistance than conventional ultrafiltration membranes (M-1 and M-2).

[0090] Example 3: Preparation of an ultrafiltration membrane with damping regions and enhanced impact resistance in a chamber

[0091] A first polymer solution consisting of 50 wt % acetone, 28 wt % dioxane, 2 wt % water, 12 wt % cellulose acetate (Acetati, Aceplast PC / FG type) and 8 wt % glycerol was applied via a doctor blade and a carriage to a PP / PE core-shell nonwoven (OMB-60; Mitsubishi) moving at 70 m / h perpendicular to the outlet opening. Directly adjacent to the carriage was a chamber with a length of 30 cm, which contained a nitrogen atmosphere as carrier gas and 19 g / m 3 1:19 mixture of ethanol:water and maintained at a constant temperature of 20°C. In the upper region of the chamber, a pretreated atmosphere stream flows through, wherein the stream is controlled so that its flow rate does not exceed 0.2 m / s, so that no eddy current occurs at the polymer film passing through the chamber in the lower region of the chamber. The chamber is operated in such a way that it always has an overpressure of 1 mbar relative to the surrounding space. The surrounding environment is subjected to suction extraction to properly remove a small amount of ethanol. After leaving the chamber, the polymer film moves perpendicular to the outlet opening of the second application medium (slide with a scraper), and a second polymer solution consisting of 50 wt% acetone, 28 wt% dioxane, 2 wt% water, 12 wt% cellulose acetate (Acetati, Aceplast PC / FG type) and 8 wt% glycerol is applied, and then transferred to a precipitation bath consisting of water at a temperature of 15°C for phase separation.

[0092] The obtained membrane is then passed through a plurality of rinsing tanks into a tank containing 50% KOH, in which the acetyl groups are hydrolyzed. The membrane is rinsed and the excess alkali is neutralized with diluted acetic acid. Relative to comparable monolayer or multilayer membranes, the regenerated cellulose membrane has a specific stability in the z direction. By crosslinking, according to the method described, for example, in DE 102004053787 A1, the membrane can be converted into a crosslinked regenerated cellulose membrane (cellulose hydrate membrane), which also has a specific mechanical stability.

[0093] Reference Symbols List

[0094] 1 Support layer

[0095] 2. First polymer solution

[0096] 3 Gas containing non-solvent (relative to the first polymer solution)

[0097] 4 Second polymer solution

[0098] 5. Sedimentation bath

[0099] 6 Rinse tank

[0100] 11 Wetting film on the bottom layer

[0101] 21 External interception surface

[0102] 22 Sponge structure (second polymer layer)

[0103] 23,33 Damping area

[0104] 24 Sponge structure (first polymer layer)

[0105] 25 Textile support layer

[0106] 46 Second polymer layer

[0107] 47 First polymer layer

[0108] K Test element

[0109] M-1 conventional ultrafiltration membrane (single-layer membrane, RC, 100kDa)

[0110] M-2 conventional ultrafiltration membrane (multilayer membrane, RC, 300kDa)

[0111] M-3 Ultrafiltration membrane of the present invention (multilayer membrane, RC, 300 kDa)

[0112] P1 Pressure obtained above the membrane (11)

[0113] P2 The pressure obtained below the membrane (11)

[0114] S Sensor

Claims

1. A method for preparing an ultrafiltration membrane, comprising the following steps: (a) applying a first polymer solution (2) to a support layer (1) to form a first polymer layer, wherein the first polymer layer penetrates into the support layer (1) to an extent of at least 25%, (b) contacting the support layer comprising the first polymer solution (2) from step (a) with a gas (3), the gas (3) comprising a non-solvent relative to the polymer in the first polymer solution (2), the contacting causing a penetration depth of the non-solvent from the atmosphere formed by the gas (3) comprising the non-solvent into the applied first polymer solution (2) of at least 5.0% but less than 80% based on the total depth of the applied first polymer solution (2), The support layer is guided through a chamber with a corresponding gas atmosphere, or the contacting is accomplished by supplying a corresponding gas flow, wherein the volume flow rate of the gas is 10 to 600 m / s (v(gas)) at a velocity of 0.3 m / s (v(gas)) to 8 m / s (v(gas)). 3 / h, wherein the gas (3) contains 1.0 g / m³ to 20 g / m³ of non-solvent, (c) applying a second polymer solution (4) to the first polymer layer to form a second polymer layer on the first polymer layer, and (d) introducing the multi-layer coated support layer into a precipitation bath (5), the precipitation bath (5) comprising a precipitation agent relative to the polymer in the first polymer solution (2) and / or the second polymer solution (4); wherein the film-forming polymer in the dissolved polymer solution is a cellulose derivative selected from the group consisting of cellulose esters, nitrocellulose and regenerated cellulose, and The support layer is a nonwoven web, a woven fabric or an open microfiltration membrane and is made of polyolefin, polyester, polyamide, polyethersulfone or regenerated cellulose, and After step (d), the first polymer layer and the second polymer layer are combined together to have a composite structure, wherein the composite structure is characterized in that the pores first widen within the second polymer layer starting from the first main surface, then the pores gradually become thinner when entering the first polymer layer in the interior of the membrane, and the pores widen again toward the second main surface during the structural change.

2. The method according to claim 1, wherein the first polymer solution (2) and the second polymer solution (4) independently have the same or different solid contents of 2 wt% to 40 wt%.

3. The method according to claim 2, wherein the first polymer solution (2) has a higher solids content than the second polymer solution (4).

4. The method according to any one of claims 1 to 3, wherein the first polymer solution (2) and the second polymer solution (4) independently have a viscosity of 800 mPa s to 40000 mPa s viscosity.

5. The method according to any one of claims 1 to 3, wherein the coating temperature in step (a) and step (c) is independently 4°C to 40°C.

6. The method according to any one of claims 1 to 3, wherein the support layer (1) in step (a) and the coated support layer in step (c) are moved at a speed of 30 m / h to 500 m / h relative to the respective polymer solution (2, 4) during coating of the respective polymer solution (2, 4).

7. The method according to any one of claims 1 to 3, wherein the gas (3) contains 1.7 g / m³ to 19 g / m³ of non-solvent.

8. The method according to claim 7, wherein the gas (3) contains 1.7 g / m³ to 18 g / m³ of non-solvent.

9. The method according to claim 7, wherein the gas (3) contains 3.0 g / m³ to 16 g / m³ of non-solvent.

10. The method according to claim 7, wherein the gas (3) contains 5.0 g / m³ to 18 g / m³ of non-solvent.

11. The method according to claim 7, wherein the gas (3) contains 5.0 g / m³ to 15 g / m³ of non-solvent.

12. The method according to claim 7, wherein the gas (3) contains 12 g / m³ to 17 g / m³ of non-solvent.

13. The method according to any one of claims 1 to 3, wherein the gas comprising a non-solvent relative to the polymer in the first polymer solution comprises nitrogen as a carrier gas and a non-solvent or a non-solvent mixture consisting of 50 vol% to 100 vol% of water and 0 vol% to 50 vol% of ethanol based on the total amount of non-solvent.

14. The method according to any one of claims 1 to 3, wherein the action time in step (b) is 500 ms to 20 s.

15. The method according to any one of claims 1 to 3, wherein the action temperature in step (b) is at least 10°C lower than the boiling point of the lowest boiling component of the first polymer solution (2), wherein the boiling point is higher than 50°C.

16. The method according to any one of claims 1 to 3, wherein step (b) is performed using a channel in which a gas stream containing a non-solvent impinges on the coated support layer at an angle of 0° to 45°.

17. The method according to any one of claims 1 to 3, further comprising the following steps: (c1) Between step (c) and step (d), the multilayer coated support layer from step (c) is contacted with a gas comprising a non-solvent for the polymers in the second polymer solution (4).

18. The method according to any one of claims 1 to 3, further comprising the steps of: (e) After step (d), the multi-layer coated support layer is introduced into one or more rinse tanks (6).

19. The method of any one of claims 1 to 3, wherein one or more of the polymer solutions comprises a cellulose ester.

20. The method according to claim 19, further comprising the steps of: (f) hydrolyzing the cellulose ester.

21. The method according to any one of claims 1 to 3, further comprising the steps of: (g) cross-linking polymer chains in the polymer layer.

22. The method according to any one of claims 1 to 3, wherein step (c) is performed one or more times before step (d), wherein different or identical polymer solutions are used, and optionally, further steps (b) are performed independently of one another between multiple steps (c), wherein the respective gas contains a non-solvent relative to the polymer in the polymer solution applied immediately before.

23. An ultrafiltration membrane obtained by the method for preparing an ultrafiltration membrane according to any one of claims 1 to 22, The ultrafiltration membrane comprises two or more polymer layers arranged one above the other on the support layer (1), and the first polymer layer arranged directly on the support layer (1) and partially in the support layer (1) or completely in the support layer (1) comprises a damping region (23, 33) on the side adjacent to the second polymer layer arranged on the first polymer layer, wherein the first polymer layer has a microporous sponge structure (24) with an average pore size of 0.05 μm to 30 μm, and the sponge structure (24) of the first polymer layer penetrates into the support layer (1) by at least 25%, and The first polymer layer and the second polymer layer are combined together to have a composite structure, and the composite structure is characterized in that the pores first widen in the second polymer layer starting from the first main surface, and then the pores gradually become thinner when entering the first polymer layer in the interior of the membrane, and the pores widen again toward the second main surface during the structural change.

24. The ultrafiltration membrane according to claim 23, wherein The convective pressure increase determined by the following test method occurs at an impact number higher than 600, wherein the test method is characterized in that a test element (K) with a diameter of 20 mm is repeatedly dropped with a force of at least 1 N but not more than 250 N onto a water-wetted ultrafiltration membrane (11) to be tested, the ultrafiltration membrane (11) being located in a housing and sealed at the top and bottom, wherein the pressure above the membrane (11) is P1 and the pressure below the membrane (11) is P2, wherein P1>P2, and a sensor (S) detects the pressure increase below the membrane (11), and wherein as soon as the membrane (11) is damaged due to the impact of the test element (K), the sensor (S) detects the convective component in addition to the diffuse component for the pressure increase.

25. The ultrafiltration membrane according to claim 23 or 24, wherein the polymer layer has a sponge structure (22, 24), and The outermost polymer layer has an outer retaining skin (21).

26. The ultrafiltration membrane according to claim 25, wherein the outer retention surface layer (21) has a thickness of 0.01 µm to 2.0 µm.

27. The ultrafiltration membrane according to any one of claims 23 to 24, wherein the support layer (1) has a thickness of 30 μm to 300 μm, The first polymer layer has a thickness of 10 μm to 100 μm, wherein the first polymer layer penetrates at least 25% into the support layer (1), The second polymer layer has a thickness of 20 μm to 100 μm, wherein the thickness of the second polymer layer is less than or equal to the thickness of the combination of the first polymer layer and the support layer (1), and The damping region (23, 33) of the first polymer layer accounts for at most 20% of the thickness of the first polymer layer.

28. The ultrafiltration membrane according to any one of claims 23 to 24, wherein the ultrafiltration membrane has a total thickness of 50 μm to 400 μm.

29. The ultrafiltration membrane according to any one of claims 23 to 24, wherein the polymer layer comprises a cellulose derivative selected from the group consisting of cellulose esters, nitrocellulose, regenerated cellulose and cross-linked regenerated cellulose.

30. The ultrafiltration membrane according to any one of claims 23 to 24, wherein the ultrafiltration membrane retains bovine serum albumin to a degree of not more than 50%.

Citation Information

Patent Citations

  • hydrated cellulose ultrafiltration membranes and process for their manufacture

    DE102004053787A1

  • Cellulose hydrate ultrafiltration membranes and method for their production

    US7422686B2

  • Abrasion-proof filtration membrane and method of producing said membrane

    CN103917287A

  • Preparation method of enhanced flat composite microporous membrane for improving hydrophility

    CN104248915A

  • High strength asymmetric cellulosic membrane

    US20030038081A1